2017
DOI: 10.1002/2017gl075238
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Origin of Groundwater Discharge to Eastern U.S. and Gulf of Mexico Coastal Waters

Abstract: Fresh groundwater discharge to coastal environments contributes to the physical and chemical conditions of coastal waters, but the role of coastal groundwater at regional to continental scales remains poorly defined due to diverse hydrologic conditions and the difficulty of tracking coastal groundwater flow paths through heterogeneous subsurface materials. We use three‐dimensional groundwater flow models for the first time to calculate the magnitude and source areas of groundwater discharge from unconfined aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 67 publications
(92 reference statements)
3
32
0
Order By: Relevance
“…Surface water bodies are less present at volcanic and limestone catchments, hence, the results of CoCa‐RFSGD and the global models were closer. This can also be seen in the model results of Befus et al (). They concluded that small catchments of their numerical model approach discharged nearly all recharge as FSGD, while the majority of catchments were larger and discharged more than 50% of recharge to the ocean.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Surface water bodies are less present at volcanic and limestone catchments, hence, the results of CoCa‐RFSGD and the global models were closer. This can also be seen in the model results of Befus et al (). They concluded that small catchments of their numerical model approach discharged nearly all recharge as FSGD, while the majority of catchments were larger and discharged more than 50% of recharge to the ocean.…”
Section: Discussionsupporting
confidence: 74%
“…Quantification of transient terrestrial groundwater fluxes into the ocean is important because shallow groundwater is an easily accessible freshwater source for the growing coastal population (Moosdorf & Oehler, 2017) that is vulnerable to anthropogenic contaminants (McCoy & Corbett, 2009). However, transient Fresh Submarine Groundwater Discharge (FSGD) is difficult to measure and regional models that quantify FSGD are only available for the Unite States (Befus et al, 2017;Sawyer et al, 2016) and Sweden (Destouni et al, 2008), which are well-monitored regions. Scientific field and modeling studies on FSGD at ungauged basins with sparse hydrogeological data availability are underrepresented, although the potential relevance of these regions has been pointed out in the past (Beusen et al, 2013;Destouni et al, 2008;Dürr et al, 2008;Seitzinger et al, 2005;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined error associated with our assumptions is difficult to quantify for the near‐global coast. However, in a comparison of 10 sites from the continental United States (Bokuniewicz, ; Bokuniewicz et al, ; Hays & Ullman, ; Mulligan & Charette, ; Reay et al, ; Russoniello et al, ; Santos et al, ; Simmons, ; Uddameri et al, ; Zimmermann et al, ), our water budget analysis yields similar estimates of fresh SGD as seepage meter studies (Sawyer et al, ), other water budget calculations, and validated three‐dimensional groundwater flow models (Befus et al, ; Zhou et al, ; supporting information Figure S1). Our estimates tend to be lower than field‐based estimates, likely because of our conservative approach for delineating coastal recharge areas, which would tend to exclude groundwater imports from upland basins.…”
Section: Methodssupporting
confidence: 67%
“…In this alternative, the terrestrially sourced fluid re‐emerges as low‐salinity springs from outcrops seaward of the coastline (Faure et al, ; Orange et al, ; Post et al, ; Puig et al, ). Fresh groundwater discharge into nearshore seawater environments has been shown previously to contribute to the physical and chemical environment of some restricted coastal waters, but the role of coastal groundwater at the larger regional to continental scales remains poorly defined (Befus et al, ; Michael et al, ).…”
Section: Models For Emission Site Depthsmentioning
confidence: 99%